Conceptual Closure Elicited by Event Boundary Transitions Affects Commercial Communication Effectiveness - Silberstein, Richard; Seixas, Shaun; Nield, Geoffrey (Frontiers in Neuroscience, 2020)
While our experience of the world may appear continuous, recent evidence suggests that our experience is automatically segmented and encoded into long-term memory as a set of discrete events. Event segmentation is an important process in long-term memory encoding with evidence pointing to experiences occurring around event boundaries being better recognized subsequently. Neuroimaging studies have shown increased activity in the hippocampus and other nodes of the Default Mode Network (DMN) when encountering an event boundary. We have previously demonstrated that the Steady State Topography (SST) measure of brain activity at a left inferior frontal scalp sites is correlated with the strength of long-term memory encoding. More recently, we have noted that event boundaries occurring in naturalistic stimuli such as television advertising trigger a transient drop in activity at the inferior frontal scalp sites, an effect we have termed Conceptual Closure. In this study, SST measures of brain activity were recorded in 50 male participants as they viewed a first-person journey through a 10-room virtual art gallery. We hypothesized that the transition from one room to another would serve as an event boundary which would triggers increased hippocampal and DMN activity while correspondingly decreasing activity in task positive networks in the vicinity of the inferior frontal cortex thus eliciting Conceptual Closure. A permutation test confirmed the hypothesis in that the appearance of the door between gallery rooms was associated with Conceptual Closure in that we observed a significant drop in brain activity at the left hemisphere inferior frontal scalp site at this point in time. Finally, we illustrate the real-world impact of Conceptual Closure by considering the commercial effectiveness of a television advertisement that exhibited Conceptual Closure at points of branding. The television advertisement was broadcast before and after it was re-edited to minimize Conceptual Closure at the time the advertising brand was being featured. Minimizing Conceptual Closure at the time of branding and key message was associated with significant increased commercial effectiveness of the advertisement.